"Being different together" in public space: young people, everyday cosmopolitanism and parochial atmospheres. (4th May 2021) - De Backer, Mattias
ABSTRACT: This paper studies the phenomenon of 'everyday cosmopolitanism' based on fieldwork and interviews with young people in the public space of Brussels, conducted between 2013 and 2016. Although the open and positive inter-cultural practices observed in public space are echoed in the tolerant attitudes expressed by these youngsters, my research also revealed the existence of racist and ethnic stereotype. This begs the question about the contingencies and the limits of this type of 'everyday cosmopolitanism'. This paper argues that that an investigation of the emergences and disappearances of tolerant attitudes can be better understood and localised by engaging in an atmospheric translation of Lyn Lofland's notion of the 'parochial realm'.